Analysis of Blood Utilization Practices and Quality Indicators in a South Indian Teaching Hospital in Puducherry, India - Purshotam Paudel; Pammy Sinha; A. Manoharan; Pooja Shri Jayakumar (Journal of Primary Care Specialties)
Introduction: The transfusion of donated blood is the mainstay of treatment for medical or surgical conditions. It is the primary responsibility of blood transfusion services to provide a safe, sufficient, and timely supply of blood products. It is recommended to conduct regular audits to know usage trends. This study aims to analyze the utilization pattern and quality indicators of transfusion services. Materials and Methods: This is a retrospective study conducted in the blood center of a tertiary care teaching hospital in Puducherry, India. We collected and analyzed data on the request and utilization of blood and its products from January 2023 to December 2023. The department-wise utilization of blood and its components, crossmatch to transfusion ratio (C: T ratio), transfusion probability (T%), and transfusion index (TI), were calculated. Results: Packed red blood cells (PRBCs) were the most utilized blood product. The intensive care unit ward received the highest blood supply, followed by obstetrics/gynecology and orthopedics. Patients with anemia, followed by surgery and pregnancy, required a majority of PRBCs. The CT ratio, TI, and TP% were 2.7%, 0.42%, and 0.37%, respectively. Conclusions: The overall transfusion indicators, namely C/T ratio, TI, and TP, were near optimal compared to standard values. However, the majority of the cross-matched blood remained unused. It is crucial to conduct a periodic review of the blood component usage in a hospital.